Effect of POFA Fineness on Durability of High Strength Concrete - Khairunisa, Muthusamy (The Associated Cement Companies Limited, 2010)
Palm oil fuel Ash (POFA) a waste from palm oil mill was used as the sole partial cement replacement material in a high strength concrete. An ordinary Portland cement concrete mix termed (PO) and two POFA concrete mixes with different fineness termed (POFA 45 and POFA 10) at 20 % replacement by weight of cement were the specimens in this study. The compressive strength, acid and chloride resistance of concrete were investigated. It was found that POFA with the higher fineness presented a better strength and durability characteristics than the other specimens.